2021
DOI: 10.3390/app112411927
|View full text |Cite
|
Sign up to set email alerts
|

Effect Mechanism of Connection Joints in Fabricated Station Structures

Abstract: The seismic response of a fabricated subway station is a complex structural connection problem that depends on the mechanical properties of the joints. In order to obtain the optimal joint distribution of a fabricated station structure under earthquake action, three finite element models of a single ring structure of fabricated subway stations assembled with seven, five, and four prefabricated components were proposed. Seismic wave characteristics, peak acceleration, and coupled horizontal and vertical seismic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A three-dimensional seismic performance evaluation model was established, providing a basic understanding of the seismic performance of the prefabricated subway station structure. He and Li (2021) studied the seismic response of the prefabricated subway station structure with different forms of joint distribution. The results showed that the seismic response of the sidewall joints was obvious with the most severe damage, making them weak joints of the fabricated station structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A three-dimensional seismic performance evaluation model was established, providing a basic understanding of the seismic performance of the prefabricated subway station structure. He and Li (2021) studied the seismic response of the prefabricated subway station structure with different forms of joint distribution. The results showed that the seismic response of the sidewall joints was obvious with the most severe damage, making them weak joints of the fabricated station structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, three papers researched deeply buried tunnels by numerical simulation. The first paper, authored by H. He and Z. Li [1], studied the optimal joint distribution of the assembled subway station structure under seismic action by the finite element software ABAQUS. The second paper, prepared by J.…”
Section: Research On Deep Rock Mass Engineeringmentioning
confidence: 99%
“…Compared with traditional buildings, assembled structures have the advantages of short construction periods and low environmental impacts, which are conducive to the construction industry's sustainable development [1][2][3][4]. Beam-column connections in assembled structures are critical cast-in-place regions where all longitudinal rebars are lapped; thus, the stress is extremely complex and prone to shear brittle failure during earthquakes, leading to the inevitable collapse of RC frame structures.…”
Section: Introductionmentioning
confidence: 99%